Forging Ahead: Biblical Archaeology’s Expanding Frontier - Darby, Erin (The Biblical archaeology review, 2025)
Biblical archaeology has come a long way in the past century. Emerging trends are reshaping how scholars think about and conduct archaeology in the biblical world. Learn how archaeologists today still grapple with the complexities of the past but also practice a more responsible archaeology that engages with a broader range of questions, geographies, and communities.